Doing justice: Gender, genre and crime in recent historical biofictions from Australia ... - Padmore, Catherine; Gardiner, Kelly (La Trobe, 2022)
In this essay we analyse three recent historical novels from Australia that take as their focus figures who transcend normative gender boundaries in some way, either through their possible criminal activity and/or their sexuality or gender identity: Hannah Kent’s Burial Rites (2013), about Agnes Magnúsdóttir, the last woman executed in Iceland; Sarah Schmidt’s See What I Have Done (2017), about the infamous Lizzie Borden; and Pip Smith’s Half Wild (2017), about the many identities of Harry Crawford. In tandem with the novels, we examine interviews and other authorial paratexts to address a number of key questions: What drew the authors to render these historical figures in fiction? What ethical or creative challenges do such portrayals present for writers and readers? What cultural work is performed by each novel? We argue that the novels’ use of indeterminacy and multiplicity as formal techniques demonstrates their authors’ commitment to feminist and revisionist interventions. Interrogating the nexus of ...